Alterations of blood monocyte subset distribution and surface phenotype are linked to infection severity in COVID‐19 inpatients. Issue 8 (6th May 2022) - Haschka, David; Petzer, Verena; Burkert, Francesco Robert; Fritsche, Gernot; Wildner, Sophie; Bellmann‐Weiler, Rosa; Tymoszuk, Piotr; Weiss, Guenter
Abstract: Severe coronavirus disease 19 (COVID‐19) manifests with systemic immediate proinflammatory innate immune activation and altered iron turnover. Iron homeostasis, differentiation, and function of myeloid leukocytes are interconnected. Therefore, we characterized the cellularity, surface marker expression, and iron transporter phenotype of neutrophils and monocyte subsets in COVID‐19 patients within 72 h from hospital admission, and analyzed how these parameters relate to infection severity. Between March and November 2020, blood leukocyte samples from hospitalized COVID‐19 patients (n = 48) and healthy individuals (n = 7) were analyzed by flow cytometry enabling comparative analysis of 40 features. Inflammation‐driven neutrophil expansion, depletion of CD16 + nonclassical monocytes, and changes in surface expression of neutrophil and monocyte CD64 and CD86 were associated with COVID‐19 severity. By unsupervised self‐organizing map clustering, four patterns of innate myeloid response were identified and linked to varying levels of systemic inflammation, altered cellular iron trafficking and the severity of disease. These alterations of the myeloid leukocyte compartment during acute COVID‐19 may be hallmarks of inefficient viral control and immune hyperactivation and may help at risk prediction and treatment optimization. Abstract : Immunophenotyping of blood myeloid leukocytes in COVID‐19 inpatients and healthy control reveals four patterns of innate response involving nonclassical monocytes, CD86, CD163, CD40 and ferroportin (FPN1) surface expression in monocytes and neutrophil levels. The response patterns are linked to disease severity, systemic inflammation, and iron turnover.